Soil and water conservation research in Peninsular Malaysia - Lai, Food See; Nik Ab. Majid, Nik Muhamad (1985)
Soil erosion and the related water problems have been a growing cause for concern in recent years. Generally, information regarding these problems is limited and fragmentary. As such the formulation of an effective soil and water conservation programmes lack the necessary base line data. This paper reviews the state of knowledge of research in soil and water conservation in Peninsular Malaysia. Some research problems and priorities are also discussed.